1952
DOI: 10.1002/jlac.19525760104
|View full text |Cite
|
Sign up to set email alerts
|

Das Verhalten einiger S‐Acyl‐aminomercaptane

Abstract: Das von F. L y n e n in der Natur aufgefundene Prinzip der energiereich gebundenen ,,aktivierten" Essigsaurel), die sich als S-Acetylderivat des Coenzyms A erwiesen hat, konnte in unserem Laboratorium erfolgreich auf Carbobenzoxy-aminosaurenz) und Aminosauren3) iibertragen werden, die sich durch Bindung an Thiophenol in energiereiche Ausgangsstoffe fur Amid-und Peptid-Synthesen uberfuhren lieBen. Im Bestreben zellverwandtere Modellsubstanzen fur eine vermutete Beteiligung einer Sulfhydrylverbindung bei der bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

1952
1952
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Cysteamine-NDBf 2 was prepared in almost quantitative yield through the reaction of cysteamine hydrochloride (1.1 eq) with NDBf-Cl 1 (1.0 eq) in refluxing ethanol and in the presence of a catalytic amount of KOAc (Scheme 1). [10][11][12][13][14][15][16][17][18] As expected the more nucleophilic sulfur of cysteamine reacts with NDBf-Cl 1 faster than nitrogen atom leading selectively to C4-S derivative 2 while no traces of the C4-N regioisomer were observed. We first decided to react 2 with different bases under mild conditions (DCM, 25 °C), in order to investigate its tendency to give the S-N-Smile rearrangement (Scheme 2, Table 1).…”
Section: A R T I C L E I N F Omentioning
confidence: 78%
See 1 more Smart Citation
“…Cysteamine-NDBf 2 was prepared in almost quantitative yield through the reaction of cysteamine hydrochloride (1.1 eq) with NDBf-Cl 1 (1.0 eq) in refluxing ethanol and in the presence of a catalytic amount of KOAc (Scheme 1). [10][11][12][13][14][15][16][17][18] As expected the more nucleophilic sulfur of cysteamine reacts with NDBf-Cl 1 faster than nitrogen atom leading selectively to C4-S derivative 2 while no traces of the C4-N regioisomer were observed. We first decided to react 2 with different bases under mild conditions (DCM, 25 °C), in order to investigate its tendency to give the S-N-Smile rearrangement (Scheme 2, Table 1).…”
Section: A R T I C L E I N F Omentioning
confidence: 78%
“…A base mediated equilibration between N-and S-acyl derivates 3a and 4a was then hypothesized and, in order to explain these results, we decided to treat compound 4a with 2 eq of Et 3 N. Quantitative conversion of 4a into 3a was observed by 1 H-NMR within 24h proving that compound 4a is the kinetic product of the reaction and compound 3a is the thermodynamic. According to Wieland and Bokelmann studies on cysteamine, 17 a plausible mechanism for the conversion of 4a into 3a is reported in Scheme 3. On the basis of this result we can assume that the treatment of 2 with Et 3 N led to 5 and addition of the ThCl after 2h led to the formation of kinetic product 4a.…”
Section: A R T I C L E I N F Omentioning
confidence: 99%
“…For this reason an acetyl group migrates more rapidly than a benzoyl group. Thus, for example, the rate of S-acetylmercaptoethylamine transformation into the corresponding thiol is higher by an order of magnitude than that of the rearrangement of S-benzoylmercaptoethylamine [635]. The acceleration of the migration of a trichloroacetyl group is even greater.…”
Section: Intramolecular Migration Of 0- N- and S-acyl Groupsmentioning
confidence: 98%
“…The MxAn method of coupling involves addition of an alkyl chloroformate (R'OCOCI) to an acid (RCOOH) in the presence of a tertiary amine to give the MxAn (RCO-0-COOR3), which is then reacted without isolation with the amino group of a second component (1)(2)(3)(4)(5). MxAn's of acylamino or peptide acids readily undergo cyclization to the 2-alkyl-5(4H)-oxazolone (6); this is the source of partial racemization that often occurs at the activated residue (5).…”
mentioning
confidence: 99%
“…Reaction of the latter with the activated species generates ester (7). AlkOx's were not known at the time of the original studies (1 -3), and ever since their development it has been suggested, without any study of the pure compounds, that MxAn's undergo decomposition via two pathways, one giving the ester and CO., the other giving the SyAn 6 and the dialkylpyrocarbonate 4 (3,5). A detailed study of MxAn's of acids not bearing a substituted amino group (RCO-0-COOR') demonstrated that both pathways indeed occur, disproportionation to the symmetrical anhydride (RC0)zO and dialkylpyrocarbonate ( R 3 0 C 0 ) 2 0 occurring at temperatures > 150°C (9, 10).…”
mentioning
confidence: 99%